Effects of storage period on seed germination of Celtis australis L. in Central Himalaya, India - Singh, Bhupendra; Bhatt, B.P.; Prasad, P. (Indian Journal of Agroforestry, 2020)
In Celtis australis, average germination was recorded to be 42.6% in fresh collected seeds, which decreased to 22.4% after eighteen months of storage at ambient room temperature, irrespective of provenance variations. Storing of seeds at low temperature (-5Â°C) was ineffective since mean germination percentage was 17.4%. Mean germination time increased during storage and average values after 18 months of storage was 23.52 and 23.59 days for the seeds stored at room temperature and cold temperature, respectively as against of 18.23 days to fresh seeds. Germination index was also higher during storage at room temperature than that of cold temperature, indicating that germination was comparatively higher and faster in the seeds stored at room temperature than those stored at low temperature.